Spectroscopic Investigation and Antifungal Studies of Some Mixed Ligand Complexes of Co(II), Ni(II) and Cu(II) with 6-Methyl-2-pyridyl Formamide Semicarbazone and Thiosemicarbazone - Rai, B.K.; Kumar, Karunesh; Srivastava, Y.P. (Asian Journal of Chemistry, 2016)
Complexes of Co(II), Ni(II) and Cu(II) with 6-methyl-2-pyridyl formamide semicarbazone and 6-methyl-2-pyridyl formamide thiosemicarbazone formed by the condensation of semicarbazide hydrochloride/thiosemicarbazide hydrochloride with 6-methyl-2-pyridyl formamide have been synthesized and their physicochemical properties have been investigated by elemental analysis, magnetic measurements, molar conductance, electronic spectra and infrared spectra. It has been observed that the ligands coordinated to the metal ion in a tridentate fashion through the nitrogen and oxygen/sulphur atoms. The ligands, 6-methyl-2-pyridyl formamide semicarbazone, 6-methyl-2-pyridyl formamide thiosemicarbazone as well as metal complexes have been screened for antifungal activity on Aspergillus flavus and Aspergillus niger.